Análise baseada em biologia de sistemas destaca processos alterados que afetam a sobrevida geral de pacientes com sarcoma de Ewing - Dalmolin, Matheus Gibeke Siqueira (2022)
Ewing’s Sarcoma (ES) is a highly aggressive disease and the second most frequent pediatric bone neoplasm. The ES hallmark is the presence of the aberrant transcription factor EWSR1-FLI that drives metabolic reprogramming. Therapeutic procedures have partially increased ES survival rate, but still present high toxicity and cause significant morbidity. To suggest more efficient therapeutic strategies, a more comprehensive understanding of the pathways that impact ES survival for development of novel diagnostics and therapeutic strategies. Here, we identified differences at the transitional level between ES patients with short-term survivors (STS) and long-term survivors (LTS) based on transcriptional data available in three public datasets, applying the transcriptogram analysis. Three differentially expressed clusters commons across the cohorts analyzed were identified. Processes related to DNA damage response and repair, immune response, apoptosis and autophagy were dysregulated between the STS and LTS groups. Furthermore, the functional enrichment of the common genes between three clusters and ES regulons highlight the upregulation of the Hippo pathway in STS patients. Our analysis suggests that different processes may be guiding the outcome of ES patients in an integrated way and may contribute to the diversity of phenotypes driven by the EWSR1-FLI1 expression fluctuation.